Plan de negocios para la elaboración y distribución de vino espumante de mortiño en el Distrito Metropolitano de Quito - Rodríguez Moreta, Jenniffer Daniela (2016)
In Ecuador, alcohol has a great cultural importance and is widely consumed at social events. In the category of wines, sparkling wines have had great growth since 2012 and are preferred by most women who appreciate elegance and glamour. However, it is increasingly expensive to import this product because of taxes and tariff surcharges. In this context domestic spirits whose prices are more competitive and are gaining more followers and can use fruits like blueberry for manufacturing high quality sparkling wine. Consequently was born the concept of Illari, a sparkling wine of intense red color with fresh and sweet flavor, made from fermenting blueberry vaccinum floribundum, which is widely known as a super fruit because of its high content of antioxidants that prevent the oxidation of cells. The target market of this product will be women of 28-59 years of the Metropolitan District of Quito. The general marketing strategy for Illari, is product development under the approach of adding new features. In addition, the marketing positioning will be more for more. The investment required for this project is USD 65.845, to be financed as follows: 40% own capital and 60% of debt, with an interest rate of 10.28% from BCE for PYMES. To determine the financial viability of this project is backed up by a financial plan, with the following results: NPV USD 89.879 and IRR 49.43%.